The Medicago truncatula DREPP Protein Triggers Microtubule Fragmentation in Membrane Nanodomains during Symbiotic Infections - Su, Chao (Plant Cell, 2020)
The initiation of intracellular host cell colonization by symbiotic rhizobia in Medicago truncatula requires repolarization of root hairs, including the rearrangement of cytoskeletal filaments. The molecular players governing microtubule (MT) reorganization during rhizobial infections remain to be discovered. Here, we identified M. truncatula DEVELOPMENTALLY REGULATED PLASMA MEMBRANE POLYPEPTIDE (DREPP), a member of the MT binding DREPP/PCaP protein family, and investigated its functions during rhizobial infections. We show that rhizobial colonization of drepp mutant roots as well as transgenic roots overexpressing DREPP is impaired. DREPP relocalizes into symbiosis-specific membrane nanodomains in a stimulus-dependent manner. This subcellular segregation coincides with DREPP-dependent MT fragmentation and a partial loss of the ability to reorganize the MT cytoskeleton in response to rhizobia, which might rely on an interaction between DREPP and the MT-organizing protein SPIRAL2. Taken together, our results reveal that establishment of symbiotic associations in M. truncatula requires DREPP in order to regulate MT reorganization during initial root hair responses to rhizobia.